Caribbean governments defend their banana growers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Banana producers elsewhere in the world are questioning the competitiveness of the Caribbean banana industry; and they do not all welcome the favourable terms of trade being offered to the Caribbean producers. How are the politicians responding? In...